The MPLEMENTASI PEMBELAJARAN RAMAH ANAK CULTURALLY RESPONSIVE TEACHING (CRT) TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS DI SDN TELUK PUCUNG VI KOTA BEKASI - Hikal Fachrizal; Yohamintin; Sunata (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2025)
This study was motivated by the low level of students’ mathematical understanding at SDN Teluk Pucung VI, Bekasi City. The objectives of this research are (1) to determine the difference in the average mathematical understanding abilities of students taught using the Culturally Responsive Teaching (CRT), and (2) to measure the extent of the influence of the CRT on the mathematical understanding abilities of fifth-grade elementary school students. The research method used was a quasi-experimental design with a nonequivalent control group design. The sample consisted of 50 students divided into two groups: 25 students in the experimental group and 25 students in the control group. The results of the study show that (1) there is a significant difference in the average mathematical understanding ability of students taught using the Culturally Responsive Teaching (CRT), and (2) the CRT has a moderate effect, with an effect size value of 0.581. It can be concluded that the use of the Culturally Responsive Teaching (CRT) is highly effective and has a positive impact on students’ mathematical understanding abilities.